Freshwater fisheries and aquaculture in China : (FAO, 1977)
This document was repared by the FAO Fisheries Mission to China which visited the Peopple's Republic of China, 21 april - 12 May 1976, to study the aquacultural and fishery practices of the country and consider ways of utilizing the Chinese experience for the further development of inland fisheries and aquaculture in other member countries of FAO.